A Study Of The Penetration And Sharpness Of Surgical Blade - Chong, Yeow Ping (2011)
Sharpness of surgical blades is an important parameter in cutting human tissues and skins. It has a critical effect on the quality of cutting (scarring, pain, sharps injury and infection transmission issues), the required energy to do the cutting, the surgery operation time and the protection for medical officers. Presently, there is no standard or protocol available to quantify the blade penetration and sharpness. In this work, a customized cutting test machine is designed and developed for the purpose of measuring the cutting force of surgical blade.